ANALISIS IMPLEMENTASI PERMENDAGRI NO 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA (STUDI KASUS PADA DESA MAMPUN BARU KECAMATAN PEMENANG BARAT KABUPATEN MERANGIN, JAMBI) - Ferdian, Tommy (Jurnal Akrab Juara, 2019)
This study aims to analyze the Implementation of Permendagri No. 113 of 2014 concerning Village Financial Management in Mampun Baru Village, Pamenang Barat District, Merangin Regency, Jambi. In qualitative research data collection is done by observation, in-depth interviews, and documentation or a combination of the three (triangulation). The results showed that based on Permendagri No. 113 In 2014, the outline of the implementation of financial management in Mampun Baru Village, Pamenang Barat District, Merangin Regency, Jambi was appropriate, but technically there were still some obstacles. These constraints such as village planning that is not timely, late reporting to the Regent, accountability reports have not been published to the community, and guidance and supervision from local governments are less than optimal. So there needs to be intensive assistance to improve village financial management in Desa Mampun Baru, Pamenang Barat District, Merangin Regency, Jambi.